The basic book of electricity and electronics - Williams, Gerald Earl. (Chicago : American Technical Society, 1979)
A textbook of electricity and electronics, including a list of suggested projects and study questions.
Spine title: Electricity and electronics.
Includes index.
Keywords: Electrical engineering; Electronics